The Causes of Domestic Violence from the Perspective of Counselors in the Covid-19 Pandemic Phenomenon - Krishnavani Gianesan; Saralah Devi Mariamdaran Chethiyar (CV. Literasi Indonesia, 2021)
The Covid-19 is one of the most sensation topics that becoming hotter among Malaysians as well as around the world. The Covid-19 Pandemic has harmed the entire society of our country as well as the foreigners around the world. Meanwhile, the issue of domestic violence is one of the most common problems during this pandemic. This study will directly emphasize the issue of domestic violence from the perspective of counselors during this Covid-19 Pandemic phenomenon. The researcher has used quantitative methods to obtain permanent data on the issue of domestic violence that occurred during the Covid-19 Pandemic. The researcher conducted an interview method with 4 registered counselors who serve in the National Population and Family Development Board and the Social Welfare Department. According to the counselor's perspective, the findings of the study show that there are several causes of the issue of domestic violence during the COVID-19 Pandemic. There are also several challenges faced by the counselors in conducting counseling sessions during the Covid-19 pandemic. Besides that, there are several proposals have been considered to enhance the study of the issue of domestic violence from the perspective of counselors in this pandemic phenomenon.